Optimization of Self-nanoemulsifying Drug Delivery System for Pterostilbene - Puspita, Oktavia Eka; Suwaldi, Suwaldi; Nugroho, Akhmad Kharis (Fakultas Farmasi, Universitas Gadjah Mada, 2016)
Solubility is prerequisite for drug absorption across absorptive cell lining the small intestine. It is a problem for poor water soluble drug because limiting its bioavailability when administered by oral route. Lipid based delivery system such as self-nanoemulsifying delivery system (SNEDDS) can be utilized in improving its solubility so that better bioavailability is achieved. Pterostilbene has extremely low solubility in water then become its limiting factor for the bioavailability. This research developed SNEDDS for oral delivery of pterostilbene. Optimum composition of SNEDDS formulation was judged by its dispersion efficiency and clarity when dispersed in water. The efficiency of this formula in enhancing bioavailability was assessed by in vitro digestion model to predict its bioavailability by determining its bioaccessibility. The result showed that optimum composition of SNEDDS was achieved by soybean oil-Croduret® 50-Span 80-PEG 400 in ratio of 16.37 %, 32.07 %, 11.56 %, and 40 %, respectively. This formula has bioacessibility of 91.48 ± 2.18 %, and it is much higher compared to pterostilbene that was not formulated into SNEDDS, i.e 4.63 ± 1.11 %. Determined by dynamic light scattering, this optimum formula has droplet size of 31.8 nm when dispersed in water.